Beetroot juice Supplementation does not improve Performance of elite 1500-m runners - Boorsma, R. K.; Whitfield, J.; Spriet, L. L. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Dietary nitrate supplementation with beetroot juice (BR) has received widespread attention as an ergogenic aid. However, recent evidence in well-trained cyclists has not consistently reported improved cycling economy or performance. The present study examined the effects of acute and chronic BR supplementation on VO2 during submaximal running and 1500-m time trial (TT) performance of elite distance runners.